Similarities and differences between the program of the University Elementary School, U.P. and the Baroda University Experimental School, India and the implications that may be derived from them - Choksi, Mahendra Manilal 1928-; Baroda University Experimental School, India ([Quezon City s.n.], 1973)
The two laboratory schools have their similarities but they also differ because of differences in the communities they serve. Both schools are under the management of universities for the training of students of education and are oriented towards educational experimentation and creative thinking. The University Elementary School in the Philippines has its own building and offers a complete elementary program from kindergarten through primary and intermediate grades while the Baroda University Experimental School does not have its own building, offers a complete elementary program (Grades 1-7) but does not offer kindergarten.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Philippines. University. Elementary School